trigonom

Level 1

in any triangle ABC : t a n A + t a n B + t a n C t a n A t a n B t a n C \frac{tan A + tan B + tan C }{ tan A tan B tan C } = ?


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Tom Engelsman
Aug 14, 2017

Let C = π ( A + B ) C = \pi - (A + B) so that t a n ( C ) = t a n ( π ( A + B ) ) = t a n ( π ) t a n ( A + B ) 1 + t a n ( π ) t a n ( A + B ) = t a n ( A + B ) . tan(C) = tan(\pi - (A+B)) = \frac{tan(\pi) - tan(A+B)}{1 + tan(\pi)tan(A+B)} = -tan(A+B). Now turning our attention to the given numerator:

N = t a n ( A ) + t a n ( B ) + t a n ( C ) t a n ( A ) + t a n ( B ) t a n ( A + B ) = t a n ( A ) + t a n ( B ) t a n ( A ) + t a n ( B ) 1 t a n ( A ) t a n ( B ) ; N = tan(A) + tan(B) + tan(C) \Rightarrow tan(A) + tan(B) - tan(A+B) = tan(A) + tan(B) - \frac{tan(A) + tan(B)}{1 - tan(A)tan(B)};

or [ t a n ( A ) + t a n ( B ) ] [ 1 t a n ( A ) t a n ( B ) ] + [ t a n ( A ) + t a n ( B ) ] 1 t a n ( A ) t a n ( B ) ; \frac{[tan(A)+tan(B)][1 - tan(A)tan(B)] + [tan(A) + tan(B)] }{1 - tan(A)tan(B)};

or t a n ( A ) + t a n ( B ) t a n ( A ) t a n ( B ) t a n 2 ( A ) t a n ( B ) t a n ( A ) t a n 2 ( B ) 1 t a n ( A ) t a n ( B ) ; \frac{tan(A) + tan(B) - tan(A) - tan(B) - tan^{2}(A)tan(B) - tan(A)tan^{2}(B)}{1 - tan(A)tan(B)};

or N = t a n 2 ( A ) t a n ( B ) + t a n ( A ) t a n 2 ( B ) 1 t a n ( A ) t a n ( B ) . N = \boxed{-\frac{tan^{2}(A)tan(B) + tan(A)tan^{2}(B)}{1 - tan(A)tan(B)}}.

Now for the denominator:

D = t a n ( A ) t a n ( B ) t a n ( C ) = t a n ( A ) t a n ( B ) [ t a n ( A + B ) ] ; D = tan(A)tan(B)tan(C) = tan(A)tan(B)[-tan(A+B)];

or t a n ( A ) t a n ( B ) t a n ( A ) + t a n ( B ) 1 t a n ( A ) t a n ( B ) ; -tan(A)tan(B) \cdot \frac{tan(A) + tan(B)}{1 - tan(A)tan(B)};

or D = t a n 2 ( A ) t a n ( B ) + t a n ( A ) t a n 2 ( B ) 1 t a n ( A ) t a n ( B ) . D = \boxed{-\frac{tan^{2}(A)tan(B) + tan(A)tan^{2}(B)}{1 - tan(A)tan(B)}}.

Since N = D N = D , the original ratio equals unity t a n ( A ) + t a n ( B ) + t a n ( C ) t a n ( A ) t a n ( B ) t a n ( C ) = 1 \Rightarrow \frac{tan(A)+tan(B)+tan(C)}{tan(A)tan(B)tan(C)} = 1 for any triangle A B C \bigtriangleup ABC .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...